Fine root dynamics and its contribution to soil organic carbon stocks with Caragana intermedia plantation development in alpine sandy land - Li, Qingxue; Jia, Zhiqing; He, Lingxianzi; Zhao, Xuebin; Yang, Henghua (Frontiers in Plant Science, 2023)
Shrubs are the main species in desert ecosystems. Better understanding shrubs fine root dynamics and its contribution to soil organic carbon (SOC) stocks can improve the accuracy of carbon sequestration estimation and provide basic data for the calculation of carbon sequestration potential. The ingrowth core method was used to investigate the fine root (< 1 mm in diameter) dynamics of Caragana intermedia Kuang et H. C. Fu plantation with different age (4-, 6-, 11-, 17-, and 31-year-old) in Gonghe Basin of the Tibetan Plateau, and the annual fine root mortality was used for calculation the annual carbon input to SOC pool. The results showed that fine root biomass, production, and mortality first increased and then decreased as the plantation age increased. Fine root biomass peaked in 17-year-old plantation, production and mortality peaked in 6-year-old plantation, and turnover rate of 4- and 6-year-old plantations were significantly higher than other plantations. Fine root production and mortality were negative correlated with soil nutrients at depth of 0–20 and 20–40 cm. The variation range of carbon input by fine root mortality across different plantation age at 0–60 cm soil depth was 0.54–0.85 Mg ha-1 year-1, accounting for 2.40–7.54% of the SOC stocks. C. intermedia plantation has a strong carbon sequestration potential from long time scale. Fine roots regenerate faster in young stands and lower soil nutrients environment. Our results suggest that the influences of plantation age and soil depth should be taken into account when calculating the contribution of fine root to SOC stocks in desert ecosystems.